An Analysis of Cultural Contents in English Textbook Used by the Eighth Grade Students of Junior High School 03 Bangkinang - Nurasia Andela; m Syafi’i S (Indonesian Journal of Integrated English Language Teaching, 2019)
The title of this thesis is “An Analysis of Cultural contents in English Textbook used by the Eighth Grade Students of Junior High School 03 Bangkinang”. This research was conducted based on some problems related to the cultural contents dissemination in the English Textbook. Absolutely, the objective of national education in Indonesia is set based on the cultural value and ideology of the nation. Thus, English textbook evaluation need to be conducted in order to know the appropriateness of the contents in the textbook. This research consisted of two formulations of the problem: how are the cultural contents disseminated in the English textbook entitled ‘English in Focus for Grade VIII (SMP/MTs), and what are the cultural contents disseminated in the English textbook. The objectives of this research are to know about how the cultural contents are disseminated in the English textbook and what are the cultural contents disseminated in the English textbook. The data of the research were collected from reading passages and also pictures in the English Textbook which was published by National Education Department. This research is a descriptive qualitative but the element of quantitative in the form of how the data are counted in a percentage has also been used. In order to know what cultural contents are disseminated in the English Textbook, the cultural contents were categorized into the source or local culture, the target culture, and the international culture (Cortazzi & Jin, 1999). Moreover, in order to know how the cultural contents were disseminated in the English Textbook, the cultural contents were categorized into four senses; the aesthetic sense, the sociological sense, the semantic sense, and the pragmatic sense (Adaskou, Britten & Fahsi, 1990).The research found that local or source culture was predominant in the textbook. The cultural contents of (43.75%) referred to the local culture, (40.62%) referred to the international culture, and (21.87%) referred to the target culture. Additionally, in order to know how the cultural contents are disseminated in textbook, the research found that generally the cultural contents were disseminated by the aesthetic sense (46.15%), the sociological sense (30.76%), and the pragmatic sense (23.07%), while the semantic sense was not found. Based on the findings, it could be concluded that the contents of English textbook in focus for grade VIII has already successfully achieved the national education goal. National characters or national culture should be input in education field.